Rancangbangun Multimedia Pembelajaran Ilmu Tajwid Guna Peningkatan Pemahaman Cara Membaca Al-Qur’an - Hindayati Mustafidah; Nurhidayah Nurhidayah (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2010)
Computer technology develops increasingly along with the development of software and hardware used. One of the fields of education, a lot of computers has played an important role. Now a lot of software is availablesupporting and improving the quality of education. One of them is a multimedia in Tajwid useful to increase understanding in learning how to read the Qur’an. This multimedia is engineered using Macromedia Flash, Adobe Photoshop CS2, Adobe Premiere Pro, Adobe After Effects 6.5, and Adobe Audition 1.5. The results of this research is learning multimedia in Tajwid which there is a discussion about the rule of nun sukun, tanwin, miem sukun, nun tasydid, miem tasydid, idghom, lam ta'rif, and makhorijulhuruf. Based on the results of testing the system on students in the TPA Al-Azhar obtained results with learning multimedia that most of the students increased their understanding in learning how to read the Qur’an. It was shown that learning multimedia can improve for understanding to read Qur’an easily. The students also get excited and find it helpful to understand how to read with the recitation of this multimedia learning science